2008
DOI: 10.1002/jor.20673
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intermittent cyclic preloads on the response of articular cartilage explants to an excessive level of unconfined compression

Abstract: Mechanical loading of articular cartilage can influence chondrocyte metabolism and lead to alterations in cartilage matrix composition. Most previous studies have focused on the effect of cyclic loading on cartilage mechanical properties and proteoglycan synthesis. However, the role of proteoglycans synthesized from cyclically loaded cartilage in response to an acute overload has not been elucidated. Therefore, we conducted studies where low intensity, intermittent cyclic loading was applied to chondral explan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…However, data from our laboratory indicated that 21 days of cyclic loading does not significantly alter the percentage of live cells ($92%) in the explants compared to unstressed controls. 8 Additionally, cyclic compression did not statistically alter the specimen thickness, suggesting no change in tissue volume over time. 8 As proposed earlier by Torzilli et al, 19 cartilage cell membrane damage may directly relate to the amount of matrix compression.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…However, data from our laboratory indicated that 21 days of cyclic loading does not significantly alter the percentage of live cells ($92%) in the explants compared to unstressed controls. 8 Additionally, cyclic compression did not statistically alter the specimen thickness, suggesting no change in tissue volume over time. 8 As proposed earlier by Torzilli et al, 19 cartilage cell membrane damage may directly relate to the amount of matrix compression.…”
Section: Discussionmentioning
confidence: 88%
“…8 Additionally, cyclic compression did not statistically alter the specimen thickness, suggesting no change in tissue volume over time. 8 As proposed earlier by Torzilli et al, 19 cartilage cell membrane damage may directly relate to the amount of matrix compression. In our current study the percentage of cell damage per unit compressive strain was significantly decreased in the cyclic preloaded explants cultured in the supplement (Fig.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…8,9 For chronic stress, few in vitro models exist, usually through high loading cycles of dynamic compression. [10][11][12] Modeling shear damage to the surface, which could be classified as a form of chronic stress, has not been well evaluated in cartilage explant studies. This is despite the clinical association between shear damage and the development of osteoarthritis (OA).…”
Section: Introductionmentioning
confidence: 99%